Discrimination Found in Zootopia Movie (Undergraduate Conference on Applied Linguistics, Linguistics, and Literature, 2022)
This research is qualitative research. The main of the study in this research are explain discrimination in Zootopia movie as well as the characters represent the discrimination in Zootopia movie. The main source of the research is a movie entitled Zootopia. The writers used some steps to analyze the movie. First, the writers searching and download Zootopia movie on the Google. Second, the writers searching and download the script of Zootopia movie on the Google. Third, the writers watched the movie in order to understand the content of the story. Fourth, the writers read the transcribed the dialog of the characters of Zootopia movie. Fifth, the writers read the script of the Zootopia movie. Sixth, the writers match between the Zootopia movie script and the Zootopia movie so that nothing is missedBased on the final results of this research, the writers suggest that the students and the readers can know and understand discrimination in Zootopia movie. The readers can be aware to discrimination and the effects of discrimination. And also, for the lecturers and the teachers, the writers suggest that the research can one of media to teach about discrimination in literature especially in analyzing discrimination in the Zootopia movie script.
Keywords: discrimination, prejudice and bias, the effects of discrimination, Zootopia movie script